Association between ABCB1 polymorphisms and response to first-generation antiepileptic drugs in a Tunisian epileptic population. (3rd August 2018) - Ajmi, Marwa; Boujaafar, Sana; Zouari, Nadia; Amor, Dorra; Nasr, Asma; Rejeb, Nabila Ben; Amor, Sana Ben; Omezzine, Asma; Benammou, Sofien; Bouslama, Ali
ABSTRACT: Purpose: We aimed in this study to investigate the association between the ATP-Binding Cassette sub-family B, member1 ( ABCB1 ) polymorphisms: C1236T (rs1128503), G2677T (rs2032582) and C3435T (rs1045642), and the resistance to antiepileptic drugs (AEDs). Materials and methods: The Polymerase Chain Reaction–Restriction Fragment Length Polymorphism genotyping of ABCB1 polymorphisms was conducted on 153 Tunisian epileptic patients treated with AEDs. Results: Two genetic polymorphisms of the ABCB1 gene seemed to influence the response to AEDs. In fact, the G2677T T and the C3435T T alleles appeared to increase the risk of developing AEDs resistance (ORs* = 3.13; 95%CI = [1.16–8.98]; p = 0.024 and ORs* = 3.10; 95%CI = [1.15–8.37]; p = 0.025), respectively. However, the C1236T T allele did not seemed to influence the response to AEDs (ORs* = 1.14; 95%CI = [0.53–3.88]; p = 0.471). Haplotypic analysis indicated high-degree linkage disequilibrium of ABCB1 polymorphisms. Our results showed a synergic effect, in fact patients with the CTT and TTT haplotypes were more likely to be drug resistant than patients with the CGC haplotype, these associations remained significant even after adjustment for confounding parameters (ORs* = 2.68; 95%CI = [1.11–8.25]; p = 0.033 and ORs* = 3.76; 95%CI = [1.69–21.05]; p = 0.006, respectively). Conclusion: The G2677T T and C3435T T alleles as well as the TT, CTT and TTT haplotypes seemed to be significantly associated with drug-resistance epilepsy in our population. Genetic predisposition, involved in this resistance, may contribute to the establishment of a personal optimized therapy for newly diagnosed epileptic patients.